2005
DOI: 10.1111/j.1600-0463.2005.apm1130103.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic changes in tubular cells from in situ kidneys following experimental hypothermia and rewarming

Abstract: Although renal failure may occur following rewarming from deep accidental hypothermia, this subject has received little attention in experimental hypothermia and clinical case reports. In order to explore the integrity of hypothermic and posthypothermic renal morphology we used an experimental animal model of accidental hypothermia where the heart supports the circulation throughout cooling and rewarming without accompanying cardioplegia or ischemia. Ultrastructural changes in renal tubular cells from three gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…It is well known that the kidney plays a role in thermogenesis, and that nephrectomized animals have lower core temperature; in these circumstances, it is quite probable that hypothermia might occur due to renal disease. Additionally, in an experimental study, hypothermia has been found to induce ultrastructural changes in renal tubular cells and these changes were similar to acute tubular necrosis . Therefore, a low body temperature might result from renal injury and may then lead to further renal functional deficiencies.…”
Section: Discussionmentioning
confidence: 97%
“…It is well known that the kidney plays a role in thermogenesis, and that nephrectomized animals have lower core temperature; in these circumstances, it is quite probable that hypothermia might occur due to renal disease. Additionally, in an experimental study, hypothermia has been found to induce ultrastructural changes in renal tubular cells and these changes were similar to acute tubular necrosis . Therefore, a low body temperature might result from renal injury and may then lead to further renal functional deficiencies.…”
Section: Discussionmentioning
confidence: 97%
“…It is known that is easier to obtain mild or moderate cooling, and that deep hypothermia is more associated with thermal injury of tissue. Also, it is important to mention that slight hypothermia has a lesser interference in the systemic temperature 4 . Although the demonstration that mild hypothermia is sufficient to offer liver protection against the deleterious actions of I/R, there are no studies concerning the kidney 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have described the various structural changes in the podocytes in challenging situations [8][9][10][11][12][13][14][15][16][17][18][19][20]. These changes include mostly foot process effacement, cell body attenuation, pseudocyst formation, and fusion of the podocytes to the GBM.…”
Section: Discussionmentioning
confidence: 99%